2015
DOI: 10.4103/0971-9784.159798
|View full text |Cite
|
Sign up to set email alerts
|

Cardioversion: What to choose? Etomidate or propofol

Abstract: Context:Electrical cardioversion is a short painful procedure to regain normal sinus rhythm requiring anaesthesia for haemodynamic stability, sedation, analgesia and early recovery.Aims:To compare propofol and etomidate as sedatives during cardioversion.Settings and Design:Single centred, prospective and randomized single blind study comprising 60 patients.Subjects and Methods:Patients more than 18 years, American Society of Anesthesiologists I/II/III grades undergoing elective cardioversion, randomly divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
3
10
0
Order By: Relevance
“…Previous studies reported a sedation duration of 7.3–15 min with etomidate or etofen, and the sedation duration of our etofen cohort is among this range. 6 , 7 , 8 , 20 Kalogridaki et al. reported that 40% of the patient in etofen group needed additional doses, which is also similar to our findings (42.1%).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Previous studies reported a sedation duration of 7.3–15 min with etomidate or etofen, and the sedation duration of our etofen cohort is among this range. 6 , 7 , 8 , 20 Kalogridaki et al. reported that 40% of the patient in etofen group needed additional doses, which is also similar to our findings (42.1%).…”
Section: Discussionsupporting
confidence: 92%
“…In previous research with etofen or etomidate alone, myoclonus was also the most commonly reported AE with a proportion of 6.6%–52%. 6 , 7 , 8 , 20 , 23 , 24 In our study, no treatment has been needed for emergence reactions, and the rate of this AE was similar to previous reports (1.8%–41.9%). 11 , 14 , 15 , 16 , 25 …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Since the introduction of etomidate as an agent for the induction of general anesthesia in 1973, [ 1 ] its use has gained popularity because of a favorable cardiovascular profile, [ 2 4 ] minimal respiratory side effects, [ 5 ] and rapid onset of action and clearance from the body. [ 6 ] Etomidate is a common choice of anesthetic drug for procedures that cause short-term pain, particularly in hemodynamically compromised patients.…”
Section: Introductionmentioning
confidence: 99%